Kontribusi A.D. Pirous dalam Perkembangan Seni Lukis Kaligrafi di Indonesia (1970-2003) - Fadhila, Annisa Nur; Jassin, Suparman (Historia Madania: Jurnal Ilmu Sejarah, 2018)
This article describes the calligraphy art in Indonesia. The focus of this study describes the contribution of A. D. Pirous in the development of calligraphy painting in Indonesia ranging from 1970-2003. The method used in this writing is a historical research method, which includes heuristics, criticism, interpretation and historiography. The result of this paper is the contribution of A. D. Pirous, in the form of a new calligraphy school (a mixture of painting and calligraphy), inspiring the use value of calligraphy painting as well as the name of calligraphy as the identity of Islamic art that is coupled with Indonesian local wisdom.